Spiritual Well-being, Self-efficacy, and Student Engagement of Muslim Juveniles during an Educational Program in Prison - Sriwiyanti, Sriwiyanti; Saefudin, Wahyu (Muslim Education Review, 2022)
The juvenile prison system in Indonesia has an educational program that aims to give the inmates rights as human beings. The juveniles are registered as students and follow various school levels such as junior high school, senior high school, and Pendidikan Kesetaraan (Paket A, Paket B, Paket C). During the educational program, they face some problematic issues and challenges. Therefore, the students need other aspects to strengthen their engagement during learning. Spiritual well-being and self-efficacy are assumed to affect and enhance engagement. Therefore, this study focuses on examining these variables. The data collection occurred on 6 January 2022. The sampling method used was a total sampling of Muslim juveniles in the Central Lombok Juvenile Prison. Respondents in this study amounted to 37 juveniles. The inclusion criteria include adolescents aged 12–18 years old who have committed various crimes, are serving time in juvenile prison, are Muslim, and follow the educational program in prison. Results are divided into two main objectives. First, students’ engagement level in attending education in prisons is high. Second, spiritual well-being and self-efficacy affect the level of student engagement. Those who have high spiritual well-being and self-efficacy scores have flourishing engagement. The findings of this study will impact various elements, such as the Directorate General of Corrections in the regulation of juvenile education, as well as teachers and educational staff in organizing schools for adolescents within the criminal justice system.